Oil palm empty fruit bunch biochar soil amendment in Amaranthus viridis cultivation to improve crop performance and soil properties - Tan, Wei Loon; Abu Bakar, Rosenani; Ahmad, Siti Hajar; Ishak, Che Fauziah (2014)
Malaysian soils are mostly classified as Ultisols and Oxisols, which are highly weathered acidic and infertile soils with low organic matter content and cation exchange capacity (CEC). Organic amendments such as compost and animal manure are needed to improve soil health for sustainable agriculture production on these soils. Application of biochar as a soil amendment is viewed as a promising alternative as it has been widely reported to improve soil quality and crop performance as well as sequestering carbon in soil due to its high carbon stability against microbial decay. A potential biochar feedstock is oil palm empty fruit bunch (EFB), a major waste from palm oil industry. The production of EFBB from EFB presents an appealing option of sustainable waste management for the oil palm industry. However, different biochars exhibit variations in characteristics, depending on feedstock and production process. Since EFBB is only recently produced, very little is known about its potential as a soil amendment for crop improvement and soil carbon sequestration. This study was conducted with the aim of investigating the effects of EFBB application on crop performance, nutrient uptake and soil properties with single and repeated application. A field study was conducted with 5 different EFBB application rates: 0 t/ha EFBB (BC0), one time application of 10 t/ha EFBB in 1 season (BC10), two applications of 10t/ha EFBB in 2 seasons (BC10+10), three applications of 10t/ha EFBB in 3 seasons (BC10+10+10) and one time 30t/ha EFBB in 1 season (BC30). The 5 biochar treatments were replicated 5 times in a RCBD layout with plot size of 1.5m x 2.0m. Three cropping cycles was established in November 2011, March 2012 and August 2012 respectively using bayam (Amaranthus viridis) as the test crop. EFBB was incorporated into the soil two weeks before transplanting. NPK 15:15:155 fertilizer was applied at the rate of 100kg N, 100kg K20 and 100kg P2O5 per hectare. Yield was recorded and plant tissue samples were collected for tissue analysis. Soil samples were taken from two different depths (0 - 20cm and 20 - 40cm) initially before planting and after each harvest for soil chemical analysis (pH, total C, total N, cation exchange capacity and exchangeable K, Ca and Mg. Soil carbon dioxide flux were also taken. Treatments with EFBB soil amendment showed significant increase in fresh yield compared to the treatment without biochar. However, there was no significant increase in yield with increasing EFBB rate. For soil properties after the first harvest, increasing EFBB rate showed significant increase in pH, and exchangeable K and Mg at 0-20 cm soil depth while exchangeable K was significant at the 20-40 cm soil depth. Similar trends were found for CEC and exchangeable K at 0-20 cm soil depth and total N and exchangeable K at 20-40 cm soil depth after the second harvest. At the third harvest, increasing EFBB application rate shows significant increase in CEC and exchangeable K for 0-20 cm soil depth and pH and exchangeable K in the 20-40 cm soil depth.